EVALUASI KINERJA SALURAN PRIMER DAN BANGUNAN SADAP UNTUK MENENTUKAN METODE PEMELIHARAAN DAERAH IRIGASI AIR NGALAM KABUPATEN SELUMA - Fanny Dwiyulitasari Edwar; Muhammad Fauzi; Besperi Besperi (Universitas Bengkulu, 2019)
This research was made to find out the performance of primary canal and tapping constructions, also inquire the maintenance that should be done and prioritized in order to maintain the irrigation. Research method was conducted through direct observation to find out water discharge and primary canal dimensions and tapping constructions, also to inventory all of damage components. Secondary data was about dimensions and canal discharge plan,rainfall data, and climatology. Climatology and rainfall calculation is used to calculate quantity of irrigation water needed. Then, this irrigation water will be used to calculate water discharge during farming season. Hydraulic calculation of primary canal and tapping construction was based on those water discharge value. Results of the research showed water discharge and dimension of primary canal and tapping constructionsat Air Ngalam can irrigate whole rice fields. Unfortunately, canal rifts and damage, and some of illegal tapping by farmersaround cause water distributing on each rice field unequal. In order to optimize Air Ngalam irrigation, it’s a must to make a sequence of action plans in highest priority, also maintenance works.